2015
DOI: 10.1007/s00269-015-0781-6
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamics and phonon dispersion of pyrope and grossular silicate garnets from ab initio simulations

Abstract: The phonon dispersion and thermodynamic properties of Mg 3 Al 2 Si 3 O 12 , pyrope, and Ca 3 Al 2 Si 3 O 12 , grossular, have been computed by using an ab initio quantum mechanical approach, an all-electron variational Gaussian type basis set and the B3LYP hybrid functional, as implemented in the CRYSTAL program. Dispersion effects in the phonon bands have been simulated by using supercells of increasing size, containing 80, 160, 320, 640, 1280 and 2160 atoms, corresponding to 1, 2, 4, 8, 16 and 27 k points in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
46
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 53 publications
(49 citation statements)
references
References 73 publications
1
46
1
1
Order By: Relevance
“…44 Beside W G , in this case a set of dynamical matrices, W k , needs to be formed for a set of wavevectors…”
Section: Phonon Dispersionmentioning
confidence: 99%
“…44 Beside W G , in this case a set of dynamical matrices, W k , needs to be formed for a set of wavevectors…”
Section: Phonon Dispersionmentioning
confidence: 99%
“…In contrast, Pavese et al () suggested that the pressure dependence of bulk modulus is lower than 3.0 from equation‐of‐state measurements. Some first‐principles studies also calculated the elasticity of grossular at static conditions (e.g., Erba, Mahmoud, et al, , Erba, Mahmoud, et al, ; Kawai & Tsuchiya, ; Mahmoud et al, ) and discussed some thermodynamics properties of grossular (Baima et al, ); nevertheless, the temperature effect on the elasticity is not available.…”
Section: Introductionmentioning
confidence: 99%
“…From the full phonon dispersion of a system, the phonon density-of-state (PDOS) can be determined, which is defined by the equation [58]:…”
Section: Phonon Dispersion and Thermodynamicsmentioning
confidence: 99%
“…The anisotropic elastic response of the system (in terms of elastic constants and directional seismic wave velocities) is investigated as a function of pressure [52][53][54][55][56]. Furthermore, the full phonon dispersion of the system is computed, which allows us to investigate other thermodynamic properties of the system and phonon density-of-states [57,58]. The Gibbs free energy of formation of CaSnO 3 from the two simple oxides CaO (cubic) and SnO 2 (tetragonal) is also evaluated as a function of temperature.…”
Section: Introductionmentioning
confidence: 99%